2020
DOI: 10.1101/2020.04.20.20073213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A model-based evaluation of the efficacy of COVID-19 social distancing, testing and hospital triage policies

Abstract: We present a stochastic compartmental network model of SARS-CoV-2 and COVID-19 exploring the e↵ects of policy choices in three domains: social distancing, hospital triaging, and testing. We distinguished between high-risk and low-risk members of the population, and modeled di↵erences in social interactions due to context, risk level, infection status, and testing status. The model incorporates many of the currently important characteristics of the disease, including overcapacity in the healthcare system and un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Recent estimates based on aggregate data from China adjusted for demography and under-ascertainment bias suggest that the overall case fatality rate of Covid-19 could be close to 1.38% [ 4 ]. However, taking into account the ratio of asymptomatic cases support infection fatality ratios hovering 0.4–0.7% [ 5 ]. These figures are lower than that of Severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), which had case fatality rates around 10% and 36% respectively [ 6 ], yet they seem to exceed those of most severe influenza strains, which have case fatality rates averaging 0.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates based on aggregate data from China adjusted for demography and under-ascertainment bias suggest that the overall case fatality rate of Covid-19 could be close to 1.38% [ 4 ]. However, taking into account the ratio of asymptomatic cases support infection fatality ratios hovering 0.4–0.7% [ 5 ]. These figures are lower than that of Severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), which had case fatality rates around 10% and 36% respectively [ 6 ], yet they seem to exceed those of most severe influenza strains, which have case fatality rates averaging 0.1%.…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic of COVID-19 is the increased risk of severe disease and death for older adults and people with comorbidities [20]. A recent COVID model captures this differential risk by distinguishing between low-risk (2/3 of all individuals in the United States) and high-risk individuals [17]. Here, we adapted this model to investigate the effects of both increased contact between individuals of the same risk group, as well as differential vaccination coverage and social distancing levels between risk groups.…”
Section: Resultsmentioning
confidence: 99%
“…or not. Then, in a more complex model developed specifically for COVID-19 [17], we add a third binary attribute distinguishing between high- and low-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…33 At the present time, while the true efficacy of these mitigation measures in controlling the current COVID-19 pandemic remain to be fully established, mathematical modeling provides insight into what is expected to occur or what may have transpired. [34][35][36] Mathematical modeling of COVID-19 transmission in Wuhan showed that the implementation of quarantine measures resulted in the R0 value decreasing from 2.65 to 1.98. This study also predicted that implementing lockdown 7 days earlier would have resulted in a 72% decrease of infected individuals.…”
Section: Mitigation Measuresmentioning
confidence: 99%